Effects of the Onset of Differential Reinforcer Quality on Skill Acquisition. Issue 4 (July 2022) - Cariveau, Tom; La Cruz Montilla, Astrid
Differential reinforcement of a target response is a necessary component of stimulus control transfer procedures. Recent research has further considered the timing (i.e., onset) of differential reinforcement of unprompted correct responding. To date, the onset of differential reinforcement has been inconsistently controlled in studies comparing skill acquisition programs for individuals with developmental disabilities. The current study serves as a systematic replication of prior comparative research to examine the effects of immediate and delayed differential reinforcement onset on the efficiency of acquisition for three individuals with developmental disabilities. The delayed onset of differential reinforcement required the fewest number of exposures to mastery per target across all comparisons. These findings failed to replicate those of prior research on differential reinforcement onset, possibly due to differences in participant characteristics, target tasks, or other required procedural modifications. Considerations for future research on differential reinforcement procedures in skill acquisition programs are described.